Determining the Risk Factors Associated with MRSA - Sonal Gupta; Bibhabati Mishra; Archana Thakur; Vinita Dogra; Poonam Sood Loomba; Manisha Jain; Aradhana Bhargava (Current Overview on Disease and Health Research Vol. 1, 2022)
The aim of the present study is to determine risk factors association with Methicillin-resistant Staphylococcus aureus (MRSA) as compared with methicillin-sensitive Staphylococcus aureus (MSSA) and to compare the minimum inhibitory concentrations (MICs) of vancomycin, teicoplanin, linezolid and erythromycin to MRSA and MSSA. A prospective study of nine months was conducted. The investigation comprised Staphylococcus aureus strains with clinical association that were identified from hospitalized individuals. E-test was used to determine the MIC of vancomycin, teicoplanin, linezolid, and erythromycin (HIMEDIA). A pre-set approach was used to assess risk variables such as immunosuppression, previous hospitalization, surgical technique performed, invasive devices, and antibiotic medication. The study comprised a total of 62 S. aureus strains. Methicillin resistance was found in 40% of S. aureus strains. MRSA was found to be highly linked with risk factors, invasive equipment, past hospitalization, and comorbid illness. Immunosuppression and antimicrobial therapy were found to have a marginally significant relationship. MRSA showed erythromycin resistance in 56 percent of cases, however MSSA showed no resistance. Teicoplanin MIC50 values and mean MIC were reported to be the lowest in vitro against MRSA and MSSA when compared to vancomycin and linezolid. Teicoplanin has not been established to be more effective than vancomycin in terms of clinical and microbiological cure, but it has a better toxicity profile and a lower risk of side effects. Minimizing risk factors and focusing on alternative drugs and infection control methods may help in MRSA infection management.